Gesture modeling and recognition using finite state machines - Pengyu Hong; Turk, M.; Huang, T.S. (4th IEEE International Conference on Automatic Face and Gesture Recognition (FG 2000), 2000)
We propose a state-based approach to gesture learning and recognition. Using spatial clustering and temporal alignment, each gesture is defined to be an ordered sequence of states in spatial-temporal space. The 2D image positions of the centers of the head and both hands of the user are used as features; these are located by a color-based tracking method. From training data of a given gesture, we first learn the spatial information and then group the data into segments that are automatically aligned temporally. The temporal information is further integrated to build a finite state machine (FSM) recognizer. Each gesture has a FSM corresponding to it. The computational efficiency of the FSM recognizers allows us to achieve real-time on-line performance. We apply this technique to build an experimental system that plays a game of "Simon Says" with the user.